Evaluasi Kapasitas dan Kinerja Lalu Lintas Simpang Berdasarkan Pedoman Kapasitas Jalan Indonesia 2023 - Haerul Bahri; Anwar Efendy; Titik Wahyuningsih; Adryan Fitrayudha (Institut Teknologi Garut, 2026)
This study aims to analyze traffic performance at the unsignalized UMMAT intersection in Mataram City based on the 2023 Indonesian Road Capacity Guidelines (PKJI). Primary data was obtained through a field survey covering traffic volume, intersection geometric conditions, and road environment characteristics during peak hours, and was then analyzed using the intersection capacity (C), degree of saturation (DJ), and traffic delay (T) parameters. The results of the study indicate that the intersection capacity is 3,524 vehicles per hour with a peak-hour traffic flow of 2,920 vehicles per hour. A degree of saturation (DJ) value of 0.83 indicates that the intersection is approaching saturation, characterized by increased vehicle interactions and limited opportunities for vehicles from minor approaches to enter the intersection. An average delay of 9.97 seconds/vehicle indicates that the intersection’s performance is in a congested state but has not yet experienced significant traffic jams. This study has limitations regarding the use of traffic data, which only represents conditions during a specific observation period and does not yet consider seasonal variations and driver behavior factors in detail. Overall, the intersection is still functioning well, but traffic management efforts are needed to anticipate a decline in performance in the future.Evaluation of Intersection Traffic Capacity and Performance Based on the 2023 Indonesian Road Capacity Guidelines